Pesticide treatment reduces hydrophobic pollutant contamination in Cucurbita pepo through competitive binding to major latex-like proteins. (November 2020) - Fujita, Kentaro; Kondoh, Yasumitsu; Honda, Kaori; Haga, Yuki; Osada, Hiroyuki; Matsumura, Chisato; Inui, Hideyuki
Abstract: Hydrophobic pollutants are still present in agricultural soil. The Cucurbitaceae family accumulates hydrophobic pollutants through roots, resulting in the contamination of aerial parts. Major latex-like proteins (MLPs), found in the Cucurbitaceae family, play an important role in the contamination by binding to these hydrophobic pollutants. Thus far, efficient cultivation methods for the production of safe crops with lower concentrations of hydrophobic pollutants have not been developed. Herein, we competitively inhibited the binding of MLPs to hydrophobic pollutants, pyrene and dieldrin, in roots by using MLP binding pesticides. By conducting a chemical array screening, we found that MLPs bound compounds with indole- and quinazoline-like structures. Commercially available pesticides amisulbrom and pyrifluquinazon, which possess such structures, successfully inhibited the binding of MLPs to pyrene and dieldrin in vitro . When zucchini plants were cultivated in the contaminated soil with 1.25 mmol/kg pyrene and 12.5 μmol/kg dieldrin, the concentration of pyrene and dieldrin in xylem sap was significantly decreased by 30% and 15%, respectively. Our results demonstrate that the pesticides binding to MLPs competitively inhibited the binding of MLPs to pyrene and dieldrin in roots, resulting in the reduction of overall contamination. This study proposes a novel approach to cultivate safer crops and advances the utilization of unknown functions of pesticides. Graphical abstract: Image 1 Highlights: The Cucurbitaceae family highly accumulates hydrophobic pollutants. Major latex-like proteins (MLPs) bound the hydrophobic pollutants pyrene and dieldrin. Binding of MLPs to hydrophobic pollutants was competitively inhibited by pesticides. Pesticides decreased the concentrations of pyrene and dieldrin in xylem sap. New strategy using pesticides to reduce contamination of zucchini was proposed. Abstract : Pesticides binding major latex-like proteins competitively inhibited the binding of MLPs to hydrophobic pollutants and decreased the concentrations of them in xylem sap of zucchini plants.